Longitudinal Evaluation of Vitamin D, Parathyroid Hormone, Antimicrobial Peptides, and Immunomodulatory Genes in Hospitalized Foals - Ahmed M. Kamr; Celine Bartish; Jamie Summers; Julia Horton; Laura D. Hostnik; Kindra Orr; Nimet Browne; Katarzyna A. Dembek; Caroline Saliba; Diego E. Gomez; Ramiro E. Toribio (Journal of Veterinary Internal Medicine)
ABSTRACT Background Information about the association of antimicrobial peptides with hypovitaminosis D in hospitalized foals is lacking. Hypothesis/Objectives We aimed to longitudinally determine the association of serum concentrations of vitamin D metabolites, vitamin D binding protein (DBP), and parathyroid hormone (PTH) with antimicrobial peptides (β‐defensin‐1 and cathelicidin‐1) and the mRNA expression of the vitamin D receptor (VDR), 1α‐hydroxylase (CYP27B1), 24‐hydroxylase (CYP24A1), toll‐like receptor‐4 (TLR‐4), tumor necrosis factor‐α (TNF‐α), interleukin‐1β (IL‐1β), disease severity, and mortality in hospitalized foals. We hypothesized that hypovitaminosis D would be associated with decreased serum concentrations of antimicrobial peptides, disease severity, and mortality in hospitalized foals. Animals One hundred nine foals ≤ 72 h of age divided into hospitalized (n = 83; 60 septic, 23 sick nonseptic [SNS]) and healthy (n = 26) foals. Methods Blood samples were collected on admission (0), and 24, 48, and 72 h after admission from healthy and hospitalized foals. Data were analyzed by repeated measure methods. Results Serum 25(OH)D, 1,25(OH)2D, DBP, β‐defensin‐1, and cathlicidin‐1 concentrations were significantly lower, whereas PTH concentrations were higher in hospitalized compared to healthy foals at different times during hospitalization (p < 0.05). Septic foals had lower VDR and CYP27B1, but higher TLR‐4, TNF‐α, and IL‐1β mRNA expression than in healthy foals (p < 0.05). Decreased serum 25(OH)D, β‐defensin‐1, and cathelicidin‐1, and high PTH concentrations were associated with higher odds of death in hospitalized foals (p < 0.05). Conclusions and Clinical Importance Decreased vitamin D metabolite concentrations and decreased antimicrobial peptide concentrations suggest that vitamin D has important immunomodulatory functions in newborn foals.